Investigating the land‑to‑sea transition in carnivorans from the evolution of sacrum morphology in pinnipeds - Esteban Núñez, Juan Miguel; Martín-Serra, Alberto; Pérez-Ramos, Alejandro; Rybczynski, Natalia; Pastor, Francisco J.; Figueirido-Castillo, Francisco Borja (Springer, 2023)
The form and function of the sacrum are of great relevance to understand the evolution of locomotion in tetrapods because it is a key piece of the vertebrate skeleton. The sacrum connects the caudal and presacral regions of the vertebral column and the hindlimbs through the pelvis. Here, we investigate sacrum shape evolution in pinnipeds (Carnivora: Pinnipedia) in relation to terrestrial mammalian carnivorans (fissipeds), and we include crown and stem taxa to quantify the morphological changes they experience in relation to the aquatic environment they inhabit. We use 3D geometric morphometric methods to explore the morphological variability and disparity of the sacrum in a set of terrestrial and aquatic carnivoran species. Our results show that the morphology of the sacrum of each pinniped family is remarkably different and that these differences may be related to the aquatic mode of locomotion (pectoral or pelvic oscillation), the use of hindlimbs to support body weight on land (otariids in contrast with phocids), and the presence or absence of a functional tail. In addition, disparity-through-time analyses indicate that the sacrum of pinnipeds is less constrained than that of fissipeds, which suggests a gravitational origin of such constraints in fissipeds. In conclusion, our results give further support to the important role played by this skeletal structure in the locomotory adaptations of mammals.
Keywords: Pinípedos - Evolución; Evolution; Fissipeds; Functional morphology; Geometric morphometrics; Pinnipeds; Sacrum